Nitrogen addition and expansion of Ligularia virgaurea drive decoupling between ammonia and nitrite oxidation - Miao Zhang; Anning Zhang; Zi Yang; Wanyu Xia; Xuanchen Liu; Xiaoxuan Jiang; Xia Zhao; Hanwen Cui; Guoliang Sha; Sa Xiao; Shuyan Chen; Beat Frey (Applied Soil Ecology, 2026)

Multifunctional aerogel with antibacterial/photothermal properties for uranium extraction from natural seawater - Zewei Hou; Zhixue Cao; Chaoxu Shen; Guoliang Nie; Zhong Liu; Jianang Sha; Peipei Yang; Songwei Li; Chuntai Liu (Desalination, 2026)

Woody Plant Encroachment Significantly Alters Grassland Soil Microbial Community: A Global Meta‐Analysis - Guoliang Sha; Shuyan Chen; Xuanchen Liu; Wanyu Xia; Hanwen Cui; Anning Zhang; Lizhe An; Zi Yang; Xia Zhao; Jing Zhang; Xiuling Yu; Jing Xiao; et al. (Global Ecology and Biogeography, 2025)
Aim Woody plant encroachment is reshaping grassland ecosystem functions worldwide. While its aboveground impacts are well documented, how this process alters microbial communities—key drivers of belowground processes—remains poorly understood. We aimed to (1) quantify the general effects of global woody plant encroachment on soil microbial community attributes in grasslands and (2) identify the abiotic and biotic factors driving these changes. Location Global grassland ecosystems. Time Period 2000–2024. Major Taxa Studied Soil microbial communities (bacteria, fungi). Methods We conducted a meta‐analysis of 241 paired observations to evaluate changes in microbial composition, diversity, biomass, activity and enzyme activity under woody plant encroachment. Results Woody plant encroachment significantly altered soil properties. Woody plant encroachment also promoted a comprehensive increase in microbial community diversity, biomass, microbial activity and enzyme activity, as well as changes in community composition. The nitrogen‐fixing status of the encroaching species (biotic factor) significantly affected microbial responses: encroachment by nitrogen‐fixing plants resulted in a higher abundance of Bacteroidetes, fungal richness, microbial biomass phosphorus and phosphatase activity compared to non‐nitrogen‐fixing plants. In addition, abiotic factors, such as mean annual temperature, soil organic carbon and total nitrogen were identified as key factors driving microbial responses. Specifically, mean annual precipitation, mean annual temperature and elevation jointly regulated the effects of woody plant encroachment on soil microbial community attributes by influencing plant and soil properties. Main Conclusions This meta‐analysis demonstrated that woody plant encroachment significantly reshaped soil microbial communities in grassland ecosystems. Our findings highlight the role of abiotic factors (climate, elevation, organic carbon and total nitrogen), and biotic factors (nitrogen‐fixing status) in mediating the response of soil microbial communities. These insights contribute to a better understanding of belowground ecological processes and provide valuable guidance for grassland management and predictions of biogeochemical cycles under global change.

Syringa oblata maintains rhizosphere r-strategists and microbial functions by regulating exudates in root tip zone under drought - Huiling Wang; Jiarui Chen; Hang Jing; Benshuai Yan; Furong Wei; Sha Xue; Guoliang Wang (Applied Soil Ecology, 2025)

Understory plant diversity supports the delivery of ecosystem multifunctionality on the Loess Plateau: A comparative of plantations and natural forests - Guoliang Sha; Huan Yu; Yuxuan Chen; Kang Ren; Pengcheng Xin; Xin Guo; Jing Xiao; Yanchao Fu (Journal of Environmental Management, 2024)

Factor contribution to soil carbon and nitrogen accumulation after vegetation restoration on the Loess Plateau, China - Yuxuan Chen; Guoliang Sha; Tianxing Wei; Kang Ren; Xin Guo; Huan Yu; Shan Jiang (Ecological Engineering, 2023)

Responses of soil microbial communities to vegetation restoration on the Loess Plateau of China: A meta-analysis - Guoliang Sha; Yuxuan Chen; Tianxing Wei; Xin Guo; Huan Yu; Shan Jiang; Pengcheng Xin; Kang Ren (Applied Soil Ecology, 2023)

Impacts of extreme weather events on terrestrial carbon and nitrogen cycling: A global meta-analysis - Qing Qu; Hongwei Xu; Zemin Ai; Minggang Wang; Guoliang Wang; Guobin Liu; Violette Geissen; Coen J. Ritsema; Sha Xue (Environmental Pollution, 2023)

Nitrogen addition enhanced water uptake by affecting fine root morphology and coarse root anatomy of Chinese pine seedlings - Guoliang Wang; Fang Liu; Sha Xue (Plant and Soil, 2017)

Nitrogen addition increases the production and turnover of the lower-order roots but not of the higher-order roots of Bothriochloa ischaemum - Guoliang Wang; Sha Xue; Fang Liu; Guobin Liu (Plant and Soil, 2017)

Root morphology and architecture respond to N addition in Pinus tabuliformis, west China - Guoliang Wang; Timothy J. Fahey; Sha Xue; Fang liu (Oecologia, 2013)